Association polymorphism of guanine nucleotide–binding protein β3 subunit (GNB3) C825T and insertion/deletion of the angiotensin-converting enzyme (ACE) gene with peripartum cardiomyopathy - Dewi, Ivana Purnama; Wardhani, Louisa Fadjri Kusuma; Maghfirah, Irma; Dewi, Kristin Purnama; Subagjo, Agus; Alsagaff, Mochamad Yusuf; Nugroho, Johanes (Frontiers in Cardiovascular Medicine, 2023)
Introduction Peripartum cardiomyopathy (PPCM) is a potentially life-threatening pregnancy-related heart disease. Genetic roles such as gene polymorphisms may relate to the etiology of PPCM. This study analyzes the association between single nucleotide gene polymorphism (SNP) guanine nucleotide–binding protein beta-3 subunit (GNB3) C825T and insertion/deletion (I/D) of the angiotensin-converting enzyme (ACE) gene with the incidence of PPCM. Methods An analytic observational study with a case–control design was conducted at the Integrated Cardiac Service Center of Dr. Soetomo General Hospital, Surabaya, Indonesia. PPCM patients of the case and control groups were enrolled. Baseline characteristic data were collected and blood samples were analyzed for SNP in the GNB3 C825T gene and for I/D in the ACE gene by using the polymerase chain reaction, restriction fragment length polymorphism, and Sanger sequencing. We also assessed ACE levels among different ACE genotypes using a sandwich-ELISA test. Results A total of 100 patients were included in this study, with 34 PPCM cases and 66 controls. There were significant differences in GNB3 TT and TC genotypes in the case group compared with that in the control group (TT: 35.3% vs. 10.6%, p = 0.003; TC: 41.2% vs. 62.5%, p = 0.022). The TT genotype increased the risk of PPCM by 4.6-fold. There was also a significant difference in the ACE DD genotype in the case group compared with that in the control group (26.5% vs. 9.1%, p = 0.021). DD genotypes increased the risk of PPCM by 3.6-fold. ACE levels were significantly higher in the DD genotype group than in the ID and II genotype groups (4,356.88 ± 232.44 pg/mL vs. 3,980.91 ± 77.79 pg/mL vs. 3,679.94 ± 325.77 pg/mL, p < 0.001). Conclusion The TT genotype of GNB3 and the DD genotype of the ACE are likely to increase the risk of PPCM. Therefore, these polymorphisms may be predisposing risk factors for PPCM incidence. ACE levels were significantly higher in the DD genotype group, which certainly had clinical implications for the management of PPCM patients in the administration of ACE inhibitors as one of the therapy options.